Pharmacokinetics of recombinant human basic fibroblast growth factor in rabbits and mice serum and rabbits aqueous humor - ZHANG Qi; WANG Guang-ji; SUN Jian-guo (Acta Pharmacologica Sinica, 2016)
AIM: To study the pharmacokinetics of recombinant human basic fibroblast growth factor (rhbFGF) in rabbits and mice after iv and postocular administration, and the changes of rhbFGF in rabbits aqueous humor after postocular administration. METHODS: After iv or postocular administration three doses of rhbFGF in rabbits and mice, rhbFGF concentration in serum and rabbit aqueous humor was determined by enzyme-linked immunosorbent assay. RESULTS: Serum concentration-time data of rabbits after iv administration of rhbFGF 1, 2, and 4 micro/kg were fitted to bi-exponential equations with half-lives of 0.9, 0.9, and 0.6 min for T1/2alpha and 7, 8, and 4.7 min for T1/2beta. Plasma concentration-time data of mice after iv administration of rhbFGF 2.5, 5 and 10 microg/kg were fitted to bi-exponential equations with half-lives of 0.4, 0.6, and 0.9 min for T1/2alpha and 6, 5, and 7 min for T1/2beta. The AUCs were linearly correlated to doses in both cases (r rabbit=0.997, r mouse=0.999). The serum concentrations of rhbFGF were very low, near to the background after postocular administration of 2 or 5 microg/kg, in both rabbits and mice. The rhbFGF levels in rabbits aqueous humor were higher than control 8 h postdose (P